2000
DOI: 10.1002/1096-9861(20001211)428:2<240::aid-cne4>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Status epilepticus-induced hilar basal dendrites on rodent granule cells contribute to recurrent excitatory circuitry

Abstract: Mossy fiber sprouting into the inner molecular layer of the dentate gyrus is an important neuroplastic change found in animal models of temporal lobe epilepsy and in humans with this type of epilepsy. Recently, we reported in the perforant path stimulation model another neuroplastic change for dentate granule cells following seizures: hilar basal dendrites (HBDs). The present study determined whether status epilepticus-induced HBDs on dentate granule cells occur in the pilocarpine model of temporal lobe epilep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
191
2
10

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(218 citation statements)
references
References 45 publications
15
191
2
10
Order By: Relevance
“…This dendrite does not extend into the molecular layer but rather toward the hilus, and it synapses with mossy fibers, thereby creating excitatory circuits similar to those formed by apical dendrites (35). The percentage of GCs that have these hilar basal dendrites is relatively small, with estimates ranging from 5 to 20% of GCs (23,(35)(36)(37). Interestingly, this estimate is sufficiently large, even at its minimum, to provide enough hubs to promote hyperexcitability according to the predictions of our model.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This dendrite does not extend into the molecular layer but rather toward the hilus, and it synapses with mossy fibers, thereby creating excitatory circuits similar to those formed by apical dendrites (35). The percentage of GCs that have these hilar basal dendrites is relatively small, with estimates ranging from 5 to 20% of GCs (23,(35)(36)(37). Interestingly, this estimate is sufficiently large, even at its minimum, to provide enough hubs to promote hyperexcitability according to the predictions of our model.…”
Section: Discussionmentioning
confidence: 74%
“…After injury, however, a subset of GCs can be found that not only have apical dendrites but a long basal dendrite as well (23). This dendrite does not extend into the molecular layer but rather toward the hilus, and it synapses with mossy fibers, thereby creating excitatory circuits similar to those formed by apical dendrites (35). The percentage of GCs that have these hilar basal dendrites is relatively small, with estimates ranging from 5 to 20% of GCs (23,(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to neuronal loss and gliosis, human and experimental mTLE pathology involves prominent dentate granule cell (DGC) abnormalities, including mossy fiber sprouting (MFS), DGCs with abnormal dendrites, and dispersed or ectopically located DGCs (Tauck and Nadler, 1985;de Lanerolle et al, 1989;Houser et al, 1990;Mello et al, 1993;Parent et al, 1997;Spigelman et al, 1998;Buckmaster and Dudek, 1999;Ribak et al, 2000;Scharfman et al, 2000;Dashtipour et al, 2001). DGC abnormalities are associated with network hyperconnectivity that may impact mTLE pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In epileptic animals, however, granule cells with basal dendrites are common (Spigelman et al, 1998;Buckmaster and Dudek, 1999;Yan et al, 2001). Basal dendrites are significant because they project into the dentate hilus and are innervated by granule cell axons in this region, creating recurrent excitatory circuits (Ribak et al, 2000;Austin and Buckmaster, 2004). By destabilizing the dentate gyrus, these circuits may contribute to hyperexcitability and seizures.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, ectopic granule cells, found in the dentate hilus of epileptic brains (Houser, 1990), receive inappropriate innervation and may also contribute to network destabilization (Scharfman et al, 2000;Pierce et al, 2005). Basal dendrites in epileptic animals are found most frequently on granule cells that, based on their migration pattern, are predicted to be newborn (Ribak et al, 2000;Dashtipour et al, 2001Dashtipour et al, , 2002Danzer et al, 2002). Similarly, at least some ectopic granule cells are derived from newborn cells (Jung et al, 2004;Jessberger et al, 2005;Parent et al, 2006).…”
Section: Introductionmentioning
confidence: 99%